PENINGKATAN KOMPETENSI GURU DALAM MENERAPKAN PEMBELAJARAN DARING MASA PANDEMI COVID 19 MELALUI PENGGUNAAN APLIKASI GOOGLE CLASSROOM SMK ISLAM INAYAH UJUNG BATU TA. 2020/2021 - Azrimelda Azrimelda (STKIP ROKANIA, 2022)
This study aims to improve the ability of teachers to implement online learning during the Covid 19 pandemic at the Inayah Ujung Batu Islamic Vocational School. This type of research is School Action Research (action research). The research conducted is a qualitative research, namely research that describes the efforts made to improve the ability of teachers in implementing online learning in the teaching and learning process. This research was carried out at the Inayah Ujung Batu Islamic Vocational School, Rokan Hulu Regency, 2020/2021 Academic Year. The subjects in this study were all teachers at the Inayah Ujun Batu Islamic Vocational School, totaling 39 teachers. Based on observations, these teachers were not optimal in implementing online learning. The results showed that in Cycle I, the understanding of teachers in online learning carried out during the learning process at SMK Islam Inayah Ujungbatu obtained a total of 1,260. The average value is 37, with a percentage of 77.20%. Thus the understanding of the teachers at the Inayah Ujungbatu Islamic Vocational School is in the Good Enough category. Then it increased after the implementation of Cycle II Online Learning which was carried out during the learning process at the Inayah Ujungbatu Islamic Vocational School, the total was 1,339. The average value is 39, with a percentage of 82.04%. Thus the understanding of the teachers at the Inayah Ujungbatu Islamic Vocational School in the Good category. The results showed that teachers' understanding of online learning at SMK Islam Inayah Ujung Batu was in the good category